The Effect of Long-Term Frozen Storage on the Quality of Meat (Longissimus thoracis et Lumborum) from Female Roe Deer (Capreolus capreolus L.) - Tomasz Daszkiewicz; Dorota Kubiak; Agata Panfil (Journal of Food Quality)
The objective of this study was to determine the quality of meat (Longissimus thoracis et lumborum) from 10 female roe deer (Capreolus capreolus L.), which was vacuum-packaged, frozen-stored (−26°C) for 6, 10, and 12 months, and compared with fresh, nonfrozen meat. Roe deer (aged 3 to 5 years) were hunter-harvested in north-eastern Poland in December and January during the same hunting season. Frozen storage did not affect the proximate chemical composition of meat (except for ash content). An analysis of the physicochemical properties of meat revealed that frozen-stored meat was characterized by a darker color, a higher hue angle, lower ability to bind its own and added water, and lower cooking loss compared with nonfrozen meat. The values noted for meat samples that were stored in the freezer for 12 months (increase in pH, considerable decrease in water-holding capacity, and first symptoms of flavor deterioration) indicate that frozen roe deer meat should be stored for no more than 10 to 12 months to maintain its high quality.